The effect of varying degrees of compression from elastic vs plastic wrap on quadriceps intramuscular temperature during wetted ice application. (24th April 2019) - Kwiecien, Susan Y.; Mathew, Stephen; Howatson, Glyn; McHugh, Malachy P.
Abstract : The aim of this study was to evaluate and compare the effectiveness of wetted ice bag, applied with high compression elastic wrap or held in place with low compression plastic wrap, on reducing vastus lateralis intramuscular temperature and skin surface temperature. Ten healthy male participants had wetted ice packs applied to a standardized area on the anterior aspect of the quadriceps simultaneously to both legs for 30 minutes. The ice pack was secured with high compression (elastic wrap) to the left anterior thigh (60.6 ± 8.1 mm Hg) and low compression (plastic wrap) to the right anterior thigh (15.5 ± 4.0 mm Hg). Intramuscular temperature (1 and 3 cm) and skin temperature of the vastus lateralis were measured continuously during a 10‐minute baseline period, 30‐minute treatment period, and a 60‐minute recovery period. No difference was observed between treatments in terms of the magnitude of reduction in intramuscular temperature at both 1 and 3 cm and skin temperature regardless of compression pressure ( P > 0.05). Temperature upon conclusion of elastic wrap treatment was as follows: 17.8 ± 5.2°C at 1 cm and 23.1 ± 4.9°C at 3 cm; plastic wrap treatment: 17.9 ± 4.4°C at 1 cm and 24.5 ± 6.7°C at 3 cm. Plastic wraps may offer a practical alternative to elastic wraps for clinicians as they may be disposed of by the patient or athlete without having to stay at the treatment facility.